2009
DOI: 10.1182/blood-2008-12-192922
|View full text |Cite
|
Sign up to set email alerts
|

Spatial gradients of blood vessels and hematopoietic stem and progenitor cells within the marrow cavities of the human skeleton

Abstract: This report evaluates the spatial profile of blood vessel fragments (BVFs) and CD34 ؉ and CD117 ؉ hematopoietic stem and progenitor cells (HSPCs) in human cancellous bone. Bone specimens were sectioned, immunostained (anti-CD34 and anti-CD117), and digitally imaged. Immunoreactive cells and vessels were then optically and morphometrically identified and labeled on the corresponding digital image. IntroductionQuantifying the spatial profile of blood vessels and primitive cell populations most susceptible to my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 9 publications
0
45
0
Order By: Relevance
“…Micro-CT permitted noninvasive imaging of the metaphyseal trabeculae in 3 dimensions and demonstrated that HSPCs in the metaphysis exist in an endosteal niche, as previously defined by us and others as within 12 cell diameters from the bone. 3,18,[22][23][24] Histomorphometric analyses of BVs in resin sections showed that all HSPCs within the metaphysis are Ͻ 3 cell diameters from a BV. Taken together, these data demonstrate that HSPCs within the metaphysis exist in an endosteal niche where they lie in close proximity to BVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro-CT permitted noninvasive imaging of the metaphyseal trabeculae in 3 dimensions and demonstrated that HSPCs in the metaphysis exist in an endosteal niche, as previously defined by us and others as within 12 cell diameters from the bone. 3,18,[22][23][24] Histomorphometric analyses of BVs in resin sections showed that all HSPCs within the metaphysis are Ͻ 3 cell diameters from a BV. Taken together, these data demonstrate that HSPCs within the metaphysis exist in an endosteal niche where they lie in close proximity to BVs.…”
Section: Discussionmentioning
confidence: 99%
“…In our and other laboratories, [22][23][24] the endosteal region is arbitrarily defined as within 12 cell diameters (ϳ 96 m) of bone. 3 Classifying transplanted HSPCs within trabecular-rich regions of bone as either central or endosteal cannot take into account trabecular bone lying just outside the plane of section.…”
Section: Hspcs Within the Metaphysis Exist In An Endosteal Niche And mentioning
confidence: 99%
“…82 Although the 3D architecture of the BM tissue in situ remains largely uncharacterized, [83][84][85][86] quantitative analysis of the interactions between these independent and dependent variables using computational modeling can aid in determining which components are more important for the specific functions of the in vivo B/BM system under normal or pathological conditions. [87][88][89] This in-depth understanding can guide the design of 3D de novo micro BM and advance investigations into disease processes using the 3D BM disease models.…”
Section: Computational Modelingmentioning
confidence: 99%
“…In contrast, there is also evidence that the osteoblast and vascular niches provide different roles in hematopoiesis, e.g. a quiescence and maintenance role verses a differentiation and egress role (Lord et al 1975;Shackney et al 1975;Gong 1978;Nilsson et al 2001;Heissig et al 2002;Arai, F. et al 2004;Balduino et al 2005;Jang and Sharkis 2007;Bourke et al 2009). Further, although these niches are proximal in the chondro-oseous region, mathematical modeling has predicted a layer of only two myeloid cells is sufficient to deplete most oxygen provided by a near by sinusoid (Chow et al 2001).…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…However, at least two hematopoietic niches have been described, an osteoblastic (or endosteal) niche, ascribed to osteoblasts residing on bone surfaces, and a vascular niche, ascribed to endothelial cells and subendothelial MSCs or pericytes lining marrow sinusoids. Many have argued that more quiescent LT-HSCs and ST-HSCs are located in the osteoblast niche, while differentiating HPCs are located in the vascular niche for mobilization to the periphery (Lord et al 1975;Shackney et al 1975;Gong 1978;Nilsson et al 2001;Heissig et al 2002;Arai, F. et al 2004;Balduino et al 2005;Jang and Sharkis 2007;Bourke et al 2009). However, these regions in the marrow are so close in proximity (Arai, F. et al 2004;Kiel et al 2005;Lo Celso et al 2009;Xie et al 2009), that the osteoblast and vascular niches may be the same, or perhaps interchangeable to some degree.…”
Section: Overview Of the Hematopoietic Nichementioning
confidence: 99%